The distribution of environmental pressures from global dietary shift - DeCesaro, Joseph; Allison, Edward (Eddie); Clawson, Gage; Frazier, Melanie; Gephart, Jessica; Hicks, Christina; Nash, Kirsty L.; Williams, David; Halpern, Benjamin (IOP Publishing, 2024)
The production and consumption of food is one of the main drivers of environmental change globally. Meanwhile, many populations remain malnourished due to insufficient or unhealthy diets. Increasingly, dietary shifts are proposed as a means to address both environmental and health concerns. We have a limited understanding of how dietary shifts could alter where food is produced and consumed and how these changes would affect the distribution of environmental pressures both globally and across different groups of people. Here we combine new food flow data linking producing to consuming country with environmental pressures to estimate how a global shift to each of four diets (Indian, EAT-Lancet, Mediterranean, and mean Food Based Dietary Guidelines (FBDGs)) could affect environmental pressures at the global, country income group, and country level. Globally, cumulative pressures decrease under the Indian, EAT-Lancet, and Mediterranean scenarios and increase under FBDGs. On average, low income countries increase their cumulative consumption and production pressures while high income countries decrease their consumption pressures, and typically decrease their production pressures. Increases in low income countries are likely due to the nutritional inadequacy of current diets and the corresponding increases in consumption quantities with a shift to our diet scenarios. Despite these increases, we believe that three out four of our simulated dietary shifts can be seen as a net benefit by decreasing global pressures while low income countries increase pressures to adequately feed their populations. Additionally, considering principles of fairness applied, some nations are more responsible for causing historical environmental pressures and should shoulder more of the change. To facilitate more equitable shifts in global diets, resources, capacity, and knowledge sharing of sustainable agricultural practices are critical to minimize the increases in pressures that low income countries would incur to adequately feed their populations.